PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN SIMULASI PHET TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI FLUIDA DINAMIS - Ramanda, Nesa; Rahmad, M.; Islami, Nur (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
In the era of technological and information development in the 21st century, it is important for students to improve their critical thinking skills in order to compete with the demands of an increasingly advanced era. Therefore, guided inquiry teaching is needed to train students to solve problems, make decisions, and develop critical thinking skills. This study aims to evaluate the effect of guided inquiry model with the help of PhET simulation on critical thinking skills of students of SMAN 5 Pekanbaru on dynamic fluid material. The research method used was Quasi Experiment with Posttest Only Control Group Design. The population of this research was all students of class XI SMAN 5 Pekanbaru, with samples of class XI Engineering 1 as the control class and XI Engineering 2 as the experimental class. The results showed a significant difference between the critical thinking skills of students taught using guided inquiry model assisted by PhET simulations with students taught using conventional learning models.